High-Throughput 96-Well Nanogroove-Enhanced Electrical Impedance Biosensor for Real-Time Label-Free Cancer Drug Screening - Choi, Jong Seob; Park, Hye-Bin; Lee, Su Han; Kim, Byunggik; Lee, Jihoon; Sung, Sang-Keun; Su, Chia-Yi; Lee, JuKyung; Jang, Seongjun; Lee, Yongjin; Lee, Jung Hyun; Kim, Hyung Jin; et al. (Advanced healthcare materials, 2025)
This study advances bioelectronic platforms and cellular behavior analysis by enhancing the precision and scalability of nanopatterned membranes integrated with electrode arrays for real-time, high-throughput monitoring. By employing self-assembled monolayers (SAMs) and optimizing imprinting parameters, uniform large-area nanopatterns are successfully fabricated, overcoming challenges such as the "rabbit ears" effect and inconsistent pattern fidelity. The nanopatterned substrates, integrated within 96-well plates with electrode arrays, enable real-time impedance spectroscopy, providing a dynamic assessment of cellular behavior under chemotherapeutic drug exposure. The developed NanoIEA platform facilitates comprehensive investigations into cellular growth and drug interactions. RNA sequencing of MCF-7 cells cultured on nanopatterned substrates reveals significant differential gene expression, suggesting that traditional flat-surface cultures may induce artificial gene regulation, potentially biasing drug screening results. Patterned cell cultures that mimic physiological conditions yield more accurate and predictive outcomes for anticancer drug screening. This research underscores the critical role of nanopatterning in recapitulating in vivo-like gene expression and highlights the profound impact of microenvironmental cues on cellular behavior. By integrating advanced nanofabrication with precise real-time monitoring, this approach addresses technical limitations in bioelectronic sensing while providing deeper insights into dynamic cellular responses, reinforcing the importance of substrate design in tissue engineering and drug development.